1997
DOI: 10.1210/en.138.8.3521
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Gonadotropins Inhibits Gonadal Tumorigenesis in Mice Transgenic for the Mouse Inhibin  -Subunit Promoter/Simian Virus 40 T-Antigen Fusion Gene

Abstract: We have previously developed a transgenic (TG) mouse model expressing the Simian virus 40 T-antigen (Tag), driven by a 6-kb fragment of the mouse inhibin alpha-subunit promoter (inh-alpha). The mice develop metastasizing gonadal tumors, of granulosa/theca or Leydig cell origin, with 100% penetrance by the age of 5-8 months. In the present study, we examined whether the appearance and growth of the gonadal tumors are dependent on gonadotropins. Gonadotropin suppression was achieved either by treatment of 3-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…The finding of high LHR expression in adrenal tumors of Inha/Tag mice evoked a question about the role of gonadotropins in adrenal tumorigenesis. We later showed that either pharmacologically or genetically induced hypogonadotropic hypogonadism prevented both gonadal and adrenal tumor development in gonad-intact Inha/Tag mice (Kananen et al, 1997), thus supporting a role for gonadotropins in tumor development. In addition, the effect of testosterone on tumorigenesis was excluded (Rilianawati et al, 2000).…”
Section: Introductionmentioning
confidence: 86%
“…The finding of high LHR expression in adrenal tumors of Inha/Tag mice evoked a question about the role of gonadotropins in adrenal tumorigenesis. We later showed that either pharmacologically or genetically induced hypogonadotropic hypogonadism prevented both gonadal and adrenal tumor development in gonad-intact Inha/Tag mice (Kananen et al, 1997), thus supporting a role for gonadotropins in tumor development. In addition, the effect of testosterone on tumorigenesis was excluded (Rilianawati et al, 2000).…”
Section: Introductionmentioning
confidence: 86%
“…It has been shown that 12 inhibin α knockout mice develop spontaneous gonadal tumors and if gonadectomized prepubertally (<6 weeks of age), they develop adrenal tumors with 99% penetrance (Matzuk et al 1994). Based on the inh -/-observations it was initially suggested that either the overexpression of gonadotropins or the lack of some gonadal factor might be the cause of tumor formation after gonadectomy (Matzuk et al 1994, Kananen et al 1996, Kananen et al 1997. Later studies have indicated that the development of tumors requires a high level of LH (Kero et al 2000) and a drop in the levels of gonadal activin, which normally inhibits the adrenal tumor growth by apoptosis (Beuschlein et al 2003).…”
Section: Transgenic (Tg) Murine Models For Adrenocortical Tumorigenesismentioning
confidence: 99%
“…If functional gonadectomy was induced by administration of a GnRH antagonist or by crossbreeding the transgenic mice into the hypogonadotropic hpg genetic background, neither gonadal nor adrenal tumors appeared [10]. This finding led to the hypothesis, that tumor development is related to elevated gonadotropin secretion, which is the distinct difference between the surgical and functional gonadectomy models (Kananen et al 1997). This high secretion of gonadotropins was thus proposed to stimulate the expression of LHR in tumors upon the malignization process .…”
Section: Adrenocortical Phenotype Of the Inhα/tag Micementioning
confidence: 99%
See 1 more Smart Citation
“…The post-castration elevation of LH levels apparently induced the ectopic LHR expression, which together with the potent oncogene Tag expression triggered adrenocortical tumorigenesis (Mikola et al 2003). LH dependence of the tumors was proven by findings that they failed to appear if the post-castration increase in gonadotropins was blocked by either treating the mice with a gonadotropin-releasing hormone antagonist or crossbreeding them to the gonadotropin-deficient hpg (hypergonadotropic) genetic background (Cattanach et al 1977, Kananen et al 1997. The adrenocortical tumors tend to grow in prepubertally gonadectomized mice by hyperplasia-adenoma-carcinoma sequence, as hyperplasia of the adrenal cortex/adrenal adenoma could be observed at the age of 4 months, whereas discernible gonadal tumors were seen only at 6 months with low metastatic incidence .…”
Section: Introductionmentioning
confidence: 99%